Hubungan Antara Dukungan Sosial dengan Berfikir Positif pada Mahasiswa Rantau yang Sedang Mengerjakan Skripsi - Irvan Rhamadani; Andhita Dyorita Khoiryasdien (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Education is a means to educate the nation's life by producing a reliable young generation. An overseas student is a student who pursues his education by migrating. This study aims to examine the relationship between social support and positive thinking in overseas students who are working on a thesis. Students who have the ability to think positively will see that the difficulties and challenges experienced when compiling a thesis as something that must be passed and consider that the challenges and difficulties will further mature themselves, both intellectually and personality. The research method used in this study is correlational quantitative method. Correlation is one or more data analysis techniques that are quantitative in nature, two or more variables are said to be correlated if changes in one variable will be followed by changes in the other variable regularly in the same direction (positive correlation) or opposite (negative correlation). The subjects in this study were active students who were writing a thesis as many as 202 students in the Special Region of Yogyakarta. Data collection is done by online distribution using google formular which measures social support and positive thinking distributed through social media, then tested using normality test, linearity test, and product moment correlation test. The results of the research conducted are that there is a very significant positive relationship between social support and positive thinking in overseas students who are working on a thesis, where this is known by the value of r = 0.933 with a significance of p = <0.000. This shows that there is a very significant positive relationship between social support and positive thinking. This study still has some shortcomings such as the research subjects in the type of college and in an unbalanced study programme, which is only on three campuses in DIY Yogyakarta.